The Effect Of Neck Pain On Craniovertebral Angle Due To The Use Of Smartphone As A Learning Media For Physiotherapy Students In Widya Husada University Semarang - Irawan Wibisono; Soesanto .; Mahalul Azam (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The COVID-19 pandemic in Indonesia affects student learning methods, one of which is the change from offline to online. Learning activities using a smartphone for a long time causes the neck position to become not ergonomic. The result will be neck pain. The purpose of this study was to determine the effect of the craniovertebral angle on neck pain in physiotherapy students at Widya Husada University Semarang. The research method using observational cross sectional. The results showed that most of the samples had normal cranivertebral angle (CVA) with mild neck pain and neck pain frequency more than 1 time per week. While the strong correlation is CVA is directly proportional to the frequency of neck pain.